The evaluation of the mechanical properties of glass, kenaf, and honeycomb fiber-reinforced composite - Zainal Abidin, Nur Marini; Hameed Sultan, Mohamed Thariq; Md Shah, Ain Umaira; Shahar, Farah Syazwani; Najeeb, Muhammad Imran; Ali, Mohd Radzi; Basri, Adi Azriff; Baloor, Satish Shenoy; Gaff, Milan; Hui, David (De Gruyter, 2023)
The development of hybrid composite materials using honeycomb structure, typically a lightweight material, is commonly used in aircraft structures. However, the use of honeycomb with natural or synthetic composite remains unexplored in the literature. Therefore, this study aims to partially replace synthetic fiber, woven glass with a natural fiber of woven kenaf and honeycomb core. An experimental analysis investigated the mechanical strength of three different compositions using glass, kenaf, and honeycomb materials for structural application purposes. The properties of the sample were evaluated through the tensile, flexural, and impact strength, and the morphological damage was observed using scanning electron microscopy. The results showed that the composition of GKGKG laminate composite is the highest in tensile strength (147.64 MPa) and modulus (3.9 GPa), while the GKHKG composite was good in flexural strength (219.03 MPa) and modulus (11.47 GPa). In terms of impact properties, there was a slight difference in energy level (20–30 J) by GKGKG and GKHKG, showing the optimal hybrid configuration of composite for the newly developed material. In conclusion, the application of the new hybrid of GKHKG composite is promising in semi-structural and structural light-weight applications.